2003
DOI: 10.1254/jphs.92.301
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Airway Goblet Cell Mucin Release

Abstract: Abstract. Airway mucus hypersecretion is one of the major clinical manifestations of patients suffering from various pulmonary diseases. However, no drugs are yet available to control airway mucus hypersecretion. For the past 15 years, a plethora of information has amassed with regard to the pharmacology of airway goblet cell mucin secretion using various primary cell culture systems. The recent discovery of various MUC genes has also greatly stimulated research in this field. Nevertheless, the heterogeneity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…Studies using apical purinergic agonists to stimulate mucin release in a wide variety of human (12,30) and animal (16,31) experimental models have demonstrated that ATP and UTP stimulate mucin secretion, most likely via an apically localized purinoceptor P2Y 2 -R. In addition to these pharmacological indications, P2Y 2 -R mRNA has been identified in SPOC1 cell (3) and in hamster (32) airway goblet cell models. Though it was intended primarily as a control in the present study, our results showing a major loss of ATP␥S-stimulated mucin secretion in P2Y 2 -R KO mouse tracheas (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies using apical purinergic agonists to stimulate mucin release in a wide variety of human (12,30) and animal (16,31) experimental models have demonstrated that ATP and UTP stimulate mucin secretion, most likely via an apically localized purinoceptor P2Y 2 -R. In addition to these pharmacological indications, P2Y 2 -R mRNA has been identified in SPOC1 cell (3) and in hamster (32) airway goblet cell models. Though it was intended primarily as a control in the present study, our results showing a major loss of ATP␥S-stimulated mucin secretion in P2Y 2 -R KO mouse tracheas (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activated P2Y-Rs couple via G␣ q to phospholipase C-␤ to cause the production of the cellular messengers IP 3 and DAG from PIP 2 , leading to Ca 2ϩ mobilization and PKC activation (62). Pharmacological studies conducted over many years with ionomycin and PMA in goblet cell models have suggested consistently that Ca 2ϩ and PKC are important in regulated mucin secretion (16,31), but mechanistic details remain elusive. Previously, we showed that nPKC␦ activation in SPOC1 cells correlates positively with regulated mucin secretion, a result that identified this isoform as a potential P2Y 2 -R downstream effector (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations